Sulfiting saba banana puree for catsup manufacture - Banzon, Marietta N.; Guzman, Matilde P. (1968)
Cooked Saba banana pulp, acidified with citric acid to pH 4, was preserved with two levels of sulfur dioxide, 1830 ppm and 3,660 ppm. Samples were stored at room temperature (70-80°F) and refrigerated temperature (40-50°F) for three weeks. These samples were tested for pH, residual SO2 content and starch content, after which they were used as base ingredient in making banana catsup. The product was evaluated by a panel composed of ten judges and was found to be acceptable
Thesis (BSFT)--University of the Philippines Diliman
Keywords: Bananas; Bananas -- Processing